2020
DOI: 10.1136/bmj.m1548
|View full text |Cite
|
Sign up to set email alerts
|

Is ethnicity linked to incidence or outcomes of covid-19?

Abstract: Preliminary signals must be explored urgently

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
481
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(513 citation statements)
references
References 9 publications
13
481
3
5
Order By: Relevance
“…Multiple reports both in the United States and the United Kingdom have shown that Covid-19 is disproportionately affecting black populations. 7 In this cohort of study participants from the United Kingdom, we found that risk of Covid-19 was over fourfold higher for black participants than for white participants. Prior to this study, data fully adjusting for comorbidities in black populations had not been reported.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Multiple reports both in the United States and the United Kingdom have shown that Covid-19 is disproportionately affecting black populations. 7 In this cohort of study participants from the United Kingdom, we found that risk of Covid-19 was over fourfold higher for black participants than for white participants. Prior to this study, data fully adjusting for comorbidities in black populations had not been reported.…”
Section: Discussionmentioning
confidence: 69%
“…6 Thiazolidinediones included rosiglitazone, troglitazone, and pioglitazone. 7 Sulfonylureas included glipizide, glibenclamide, glibornuride, gliclazide, gliquidone, acetohexamide, tolbutamide, chlorpropamide, and tolazamide.…”
Section: Copyright/license For Publicationmentioning
confidence: 99%
“…It remains uncertain, for example, whether ethnicity is associated with the incidence of severe covid-19 or with a worse outcome after developing severe disease. 13 Understanding population-level risk factors for covid-19 is of major interest to the general public and public health bodies, and will underpin strategies for population-wide disease prevention.…”
Section: Introductionmentioning
confidence: 99%
“…While first systematic reviews about COVID-19 incidences from China relied on ethnically homogenous cohorts, 17,18 ethnically diverse populations, such as in the U.K. and U.S. may exhibit different susceptibility or response to infection because of socioeconomic, cultural, or lifestyle factors, genetic predisposition and pathophysiological differences. Certain vitamin or mineral deficiencies, differences in insulin resistance or vaccination policies in countries of birth may also be contributing factors.…”
Section: Racial Compositionmentioning
confidence: 99%
“…Certain vitamin or mineral deficiencies, differences in insulin resistance or vaccination policies in countries of birth may also be contributing factors. 18 We include variables measuring the composition of U.S. counties regarding racial and ethnic groups.…”
Section: Racial Compositionmentioning
confidence: 99%